Survey of Monitoring Policy on Access to and Use of the Internet in Selected University Libraries in South-Western, Nigeria - Chima, Ogbuiyi, Darlina; Daniel, Oriogu, Chuks; Onyebuchi, Chukwuemeka, Anthony; O, Allison, Goodluck (American Journal of Education and Learning, 2016)
The paper presents the survey of monitoring policy on access to and use of the Internet in selected university libraries in South-western, Nigeria. It shows the relevance of Internet monitoring policy, ways of Internet monitoring policy, items, sites and activities to be monitored in university libraries in Nigeria. Thus, the study suggested the need for monitoring policy on access to and use of Internet in University libraries in Nigeria in order to create an enabling environment for proper use of Internet for academic purposes by students.